Mengintegrasikan Sikap Nasionalisme dalam Pembelajaran Kimia Berbasis Kearifan Lokal pada Materi Sifat Koligatif Larutan - Listia Fauziyyah Ahmad (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Chemistry learning in senior high schools (SMA) is seen as abstract and theoretically oriented, making it less contextually meaningful for students. The integration of national values of patriotism and the use of local wisdom in science learning, especially chemistry, is still limited compared to social subjects. This study aims to examine the integration of local wisdom in chemistry learning on the colligative properties of solutions through the practice of making salted eggs (a traditional Indonesian food product) as an effort to foster patriotic character education. The research method used is descriptive qualitative with 34 students of grade XI as subjects. Data were obtained through a response questionnaire and analyzed descriptively in the form of percentages. The results of the study showed an increase in the attitude of patriotism through reflection on local wisdom-based chemistry learning, increasing students' awareness of the scientific and cultural value of local products, encouraging a commitment to be proud of innovating and developing local products that can improve the welfare of the Indonesian people, not just for consumption but also for cultural heritage that can be developed scientifically and economically. The integration of science and culture in this learning was able to increase student involvement in the learning process, facilitate the understanding of chemical concepts, and show the meeting point between understanding chemical concepts and strengthening the character of patriotism, and is in line with the Pancasila Student Profile and the principles of meaningful contextual learning.